Landscapes of Fear - Tuan, Yi-fu, 1930- (Book collections on Project MUSE., 1979)
Landscapes of Fear is renowned geographer Yi-Fu Tuan's influential exploration of the spaces of fear and of how these landscapes shift during our lives and vary throughout history. In this groundbreaking work-now with a new preface by the author-Yi-Fu Tuan reaches back into our prehistory to discover what is universal and what is particular in our inheritance of fear.